(untitled) (Journal of Hama University, 2024)
Dry mouth includes two possible manifestations, the first of it is subjective, Indicates the patient’s personal feeling of dryness in the oral cavity and is called "Xerostomia", The other is a measured value that indicates the function of the salivary glands "Salivary gland hypofunction". The aim of the research was to study the prevalence of Xerostomia and analyze the relationship between it and smoking habit.The research was conducted on a sample of (n = 400) patients, the mean age of the participants was (33.4 ± 14.6), a self-questionnaire was distributed randomly, Demographic information was collected (name, age, gender). Patients were asked to answer the five items of the Summated Xerostomia Inventory-Dutch (SXI-D) and were also asked about their smoking habit. Statistically, chi-square test was used to assess the relationship among the categorical variables. The prevalence of xerostomia in the study sample was (26.3%), about (28%) of females had xerostomia higher than males (23.8%), but without statistical significance, dry mouth was not associated with age (P = 0.652), and the prevalence of Xerostomia was higher in non-smokers (61%) compared with smokers (35.2%) and the incidence of xerostomia was not associated with smoking habit.The prevalence of xerostomia was higher among patients. This condition was observed in females more than males, it was not associated with age, and was not associated with smoking habits. The dentist must be familiar with how to diagnose Xerostomia and know the symptoms of this disease in order to control it, reduce complications related to it and treat it optimally.